The reality of applying total quality management and its role in promoting sustainable development The Environment of Higher Education Institutions: "Theoretical Review" (Journal of Human Sciences, 2022)
The study reviews the reality of the application of total quality management and its role in promoting sustainable development in higher education institutions. A number of results, the most important of which is that higher education in Libya is traditional, where it is limited to providing knowledge only, the low level of scientific research, and the lack of financial support, as well as the relentless pursuit of quality management in higher education institutions to progress and advance in the provision of a modern advanced management that provides the best services to the internal and external community to meet the needs of and the adequacy of the labor market, and it reached a number of recommendations, the most important of which is to urge senior leaders in departments and departments of academic accreditation and quality in Libyan universities to embrace the principle of total quality management, and to adopt the benchmarking approach to improve the quality of performance and services of these universities and support them, and to apply this approach with international and international universities.